Digital sesame information systems: IPSR Innovation Profile - Kassie, Girma T.; Abate, Gashaw T.; Worku, Y.; Asnake, Woinishet; Minot, Nicholas (CGIAR System Organization, 2024)
A digital information system that enables the efficient collection, processing, and distribution of information on weather and sesame marking. The weather data will be about temperature and precipitation. The marketing data will focus on input and output prices, sesame supply, quantity demanded, and new regulations.